2008
DOI: 10.1063/1.2890073
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient laser action in femtosecond-written Nd:yttrium aluminum garnet ceramic waveguides

Abstract: We report continuous wave 1.06 m laser operation in an optical waveguide fabricated in a Nd:YAG ceramic by femtosecond laser writing. Single mode and stable laser oscillation have been achieved by using the natural Fresnel reflection for optical feedback. Output laser power in excess of 80 mW and a laser slope efficiency of 60% have been demonstrated. © 2008 American Institute of Physics. ͓DOI: 10.1063/1.2890073͔Femtosecond direct laser writing ͑DLW͒ of transparent materials is attracting much attention becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(105 citation statements)
references
References 20 publications
(24 reference statements)
1
100
1
3
Order By: Relevance
“…Thus a waveguide is usually created in the area adjacent to tracks written by femtosecond beam. Since in this case waveguiding is due to an indirect effect accompanying femtosecond modification of crystal lattice, magnitude of refractive index change in the waveguide is not so high as in glass waveguides and does not exceed 1*10 -3 (Nejadmalayeri, 2005;Torchia, 2008;Siebenmorgen, 2009;Silva, 2010;Bookey, 2007;. This value is not enough to build compact waveguide lasers with diode pumping.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus a waveguide is usually created in the area adjacent to tracks written by femtosecond beam. Since in this case waveguiding is due to an indirect effect accompanying femtosecond modification of crystal lattice, magnitude of refractive index change in the waveguide is not so high as in glass waveguides and does not exceed 1*10 -3 (Nejadmalayeri, 2005;Torchia, 2008;Siebenmorgen, 2009;Silva, 2010;Bookey, 2007;. This value is not enough to build compact waveguide lasers with diode pumping.…”
Section: Introductionmentioning
confidence: 92%
“…The 1 kHz Ti:Sapphire laser always produces a negative PRICE in YAG single crystals (Okhrimchuk, 2005(Okhrimchuk, -a, 2005Siebenmorgen, 2009). It was reported that in the ceramic YAG doped with 2 at.% of Nd 3+ ions PRICE is negative too (Torchia, 2008). However there is refractive index increase in the area closely adjacent to a track (Dubov, 2004;Siebenmorgen, 2009) that is due to elasto-optical effect.…”
Section: Waveguide Fabrication Technique and Architecturementioning
confidence: 99%
“…More details about these waveguides can be found elsewhere. 7 As commented before, these waveguides did not show any lattice re-distribution so they behave as homogeneous line broadened laser sources. In this case, the laser threshold was also close to 60 mW, i.e., similar to that of MS-DLW WGs.…”
Section: Resultsmentioning
confidence: 91%
“…4 I 11/2 transition of Neodymium ions). 7,8,15 One of the main drawbacks of Nd:YAG DLW waveguides fabricated with low repetition rate lasers is the unavoidable damage and stress, as well as the impossibility of writing increased step-index type waveguides. The importance of being able to inscribe step-index increased waveguides (Type I WGs in the following), relies on the fact that these type of waveguides (step-index direct written cores) could exhibit superior light confinement and lower bend losses, as well as much more controllable mode dispersion properties, than stress-induced waveguides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation